Monitoring in the operating room. What’s new? - S.M. Nedashkivskyi; D.O. Dzyuba; B.I. Kedyo (Медицина неотложных состояний, 2023)
The article deals with new requirements for intraoperative monitoring. The requirements that allow increasing the safety of the patient’s stay in the operating room are being expanded. Special attention is paid to patients in a sub- and decompensated state, patients with comorbid diseases. Monitoring is based on the recommendations of the Association of Anaesthetists of Great Britain and Ireland, which were reviewed and updated in 2021.